The educational paradigm within modern liquidness - Ugarte Calleja, Sebes (Historia y Comunicación Social, 2014)
Approaching the modern educational system is currently a journey full of uncertainties. Not so many years ago, we used to think that a change of paradigm required a change of tools; however, blockade by ‘infoxication’ and outside arguments make it unfeasible to find a balance between education and what is happening to us. This essay addresses the topic of judgement in education and, above all, the need to use it creatively, enabling our understanding capacity, our emotional intelligence and our full awareness.
Keywords: Communication; Social Media; Liquid Education; Education System; Creativity; Criterion; Emotional Intelligence; Flow; Csikszentmihalyi; Robinson; Goleman.